The Development of Pasar Rabu Tani Android Based Application - Meri Azmi; Yance Sonatha; Siti Sa'adiyah (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2022)
Pasar Rabu Tani is a business organized by the Koperasi Mandiri dan Merdeka (KMDM) which consists of a number of Andalas University academics which aims to provide healthy food needs to consumers. So far, in marketing its products, KMDM uses various media platforms such as whatsapp, google form and Instagram. The goal of this research is to produce an application that provides convenience for consumers and producers in meeting the needs of healthy food. The method used to develop this application is the waterfall method. This application was developed using android, flutter framework, JSON (JavaScript Object Notation). The final result of this research is an application that can be accessed through various smartphone devices. With the Pasar Rabu Tani application, it will be a good thing for the community to meet their food needs by staying at home but being able to shop for healthy food needs quickly and accurately. Pasar Rabu Tani, merupakan sebuah usaha yang diselenggarakan oleh Koperasi Mandiri dan Merdeka(KMDM) yang beranggotakan sejumlah akademisi Universitas Andalas yang bertujuan untuk menyediakan kebutuhan pangan sehat pada konsumen. Selama ini dalam pemasaran produknya, KMDM menggunakan berbagai platform media seperti whatsapp, google form dan instagram. Penelitian ini bertujuan untuk menghasilkan sebuah aplikasi yang memberikan kemudahan bagi konsumen dan produsen dalam memenuhi kebutuhan pangan yang sehat. Metode yang digunakan untuk mengembangkan aplikasi ini adalah metode waterfall. Aplikasi ini dikembangkan dengan meggunakan android, framework flutter, JSON (JavaScript Object Notation). Hasil akhir dari penelitian ini adalah aplikasi yang dapat diakses melalui berbagai perangkat smartphone. Dengan adanya aplikasi Pasar Rabu Tani ini memudahkan masyarakat dalam memenuhi kebutuhan pangan dengan tetap dirumah saja tetapi dapat berbelanja kebutuhan pangan sehat dengan cepat dan tepat.